Analisis Tingkat Pengembalian Investasi Saham Lq-45 Tahun 2015 - Farida, Ana Bintan; Yuliaty, Erma (JHP17 (Jurnal Hasil Penelitian), 2018)
The LQ-45 stock index is an index of 45 stocks selected because of its goodfundamentally good performance so that its capitalization continues to show progress.Therefore, LQ-45 shares are stocks that are in great demand by investors and are believed toprovide a positive rate of return that exceeds the risk. In this connection, research is conductedto ensure LQ-45 stock performance by using Single Index Model. The hope of this study is thatif indeed the stocks incorporated in the LQ-45 index are able to provide abnormal positivereturns significantly, LQ-45 stocks are eligible to be selected as part of the investor portfolio.The results showed that of 40 LQ-45 stocks selected for study showed that 17 stocks resulted inabnormal average returns above zero (positive) and 23 stocks resulted in abnormal averagereturns below zero (negative). However, after statistically tested between abnormal positive andabnormal returns the negative rate of return is the rate of return is not different from zero. Thus,the selected shares in the LQ-45 index are not able to give a significantly positive abnormalreturn rate which means that the LQ-45 stock is only capable of providing the same rate ofreturn as the risk..Keywords: LQ-45 Stocks, Abnormal Return,Single-Index Model .